The influence of antecedent factors on corporate entrepreneurship and innovative performance relationship - Rosle Mohidin; Amer Azlan Abdul Jamal; Caroline Geetha Arokiadasan; Rasid Mail; Zaiton Osman (2012)
The study attempts to investigate managers’ perception on the influence of antecedent factors that stimulate corporate entrepreneurship relationship with innovative performance. The data used in this study represents managers that currently employed in Sabah Electricity Sdn. Bhd. (SESB), the sole provider of electricity in the state of Sabah, Malaysia. A total of 110 managers participated in this survey which came from various managerial levels in the organization. The finding of this study reveals that both Intelligence Generation Factor (IGF) and Internal Organization Factors (IOF) do not foster corporate entrepreneurship creation in relation to innovative performance in SESB. In order to generalize the finding, it is recommended further study should not only concentrate in one particular organization but a comprehensive study should be conducted on various organizations in the same industry in order to capture differences in entrepreneurship practices. Lastly, the unit of analysis should not only be restricted to only managers but the study should consider all employees in the organization.